Evaluating a pedagogical approach to promoting academic integrity in higher education: An online induction program - Sbaffi, Laura; Zhao, Xin (Frontiers in Psychology, 2022)
Academic integrity is at the heart of excellent education. However, resources explaining the concept tend to be definition-driven, while using complex language and sometimes even an austere tone designed to discourage students from breaches. This study aims to design and evaluate an online module at a UK University across two years, designed to improve students’ understanding of concepts of academic integrity and practice. The module includes a range of interactive resources (e.g., gamified quizzes and e-booklets) and was made available to a large cohort of postgraduate students (448). The study adopts a mixed-methods approach composed of three sequential phases involving first collecting students’ views on existing academic integrity resources (7 students participating in a focus group and 39 competing a questionnaire), then developing a range of new ones based on students’ feedback to form the content of the module, and finally gathering students’ evaluation on the newly created resources (sample size: 361 students). Results illustrate a clear improvement in relation to the accessibility, usefulness and understandability of new resources. Results also highlight a remarkable increase in student confidence levels regarding academic integrity. Students also considered the new module as more appealing and informative. This paper offers a good example of a pedagogical approach aimed at promoting academic integrity in an innovative and engaging fashion.